Pecvd in-situ growth of silicon quantum dots in dielectric matrix for third generation photovoltaics - Usatîi, Iurie (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2009)
Silicon nanostructures have interesting possible applications in third generation photo-